Eksplorasi Senyawa Penghambat Enzim Salisilat Sintase dari Mycobacterium tuberculosis melalui Studi Penambatan Molekul dan Prediksi Sifat ADME: Exploration of Salicylate Synthase Enzyme Inhibitors from Mycobacterium tuberculosis Through Molecular Docking Studies and ADME Properties Prediction - Arfan Arfan; Rahmat Muliadi; Nur Rayani (Fakultas Farmasi Universitas Halu Oleo, 2023)
The emergence of drug-resistant Mycobacterium tuberculosis (MTB) has become a major issue in tuberculosis (TB) treatment, and needs to find and develop new efficient drugs for better TB control. This research aims to discover a potential MTB salicylate synthase inhibitor, which regulates mycobactin biosynthesis, to bind iron ions which facilitate bacteria to replicate by utilizing the molecular docking method. A total of 462 compounds were chosen from the Marine Natural Products database. The test compounds were filtered sequentially based on their molecular weight and binding affinity energy. After re-categorizing the parameters, such as predicted binding energies and molecular interactions, including hydrogen bond and hydrophobic interactions, compounds CMNPD18535 (xylogranatin H), CMNPD20622 (agallochoal O), CMNPD25719 (isoscutellarein 7-O-β-xyloside-2′′-O-sulfate), and CMNPD31560 (28-nor-olean-2a,3ß-dihydroxy-14,17-diene-16-one) were identified as hit compounds. These four compounds demonstrated the greatest ability to inhibit the salicylate synthase enzyme with binding energies of -10.33, -10.1, -10.03, and -9.76 kcal/mol, respectively, compared to RVE (native ligand), which exhibited binding energy of -8.15 kcal/mol. Overall, the hit compounds showed a relatively good safety profile and Lipinski criteria except for CMNPD20622 because it inhibits the enzymes CYP2C9 and CYP3A4, and CMNPD25719, which has excess donors and acceptors hydrogen, thus violating 2 Lipinski criteria as an oral drug. This research could be the first step toward identifying appropriate candidate compounds for further experimental investigation as an alternative to the MTB salicylate synthase inhibitors.